FINDING THE COMMON THREAD OF THE INDONESIAN VS UNITED STATES EDUCATION SYSTEM - Loka, Sindi Ceriya; Al Fares, Muhammad; Puspita, Lidiya; Koto, Irwan (MEDIA DIDAKTIKA, 2025)
This study aims to analyze and compare the education systems in Indonesia and the United States, focusing on the Educational Goals and Philosophies of the Two Countries, Curriculum, Learning Methods, Role of Teachers and Teacher Training, Evaluation and Assessment, Equitable Access to Education and the Use of Technology in Education applied in both countries. In the context of globalization and the development of information technology, a deep understanding of the differences and similarities in this education system has become very important. The research methods used are literature studies and comparative analysis, which involves collecting data from various sources, including official documents, scientific articles, and educational reports. The results show that despite significant differences in the approach and implementation of the education system, the two countries have the same goal, which is to create a competent generation ready to face global challenges. This study also found that cultural, economic, and government policy factors play a major role in shaping the characteristics of each education system. Thus, this research is expected to provide broader insights for educators, policymakers, and researchers in an effort to improve the quality of education in Indonesia and the United States.